Penerapan Business Logic Component dalam aplikasi penjualan dan edukasi produk hidroponik berbasis mobile - Mulyani, Esti; Bunga, Munengsih Sari; Gozali, Ahmad Lubis; Nurhanudin, Aldi; Udin, Sahrul Fazri (Universitas Merdeka Malang, 2023)
In advanced technology and internet era, daily activities such as shopping, working, studying, and communicatingbecame more efficient and faster. This provides a great opportunity to improve the quality of life and the development of the mind. However, there are challenges faced by hydroponic farmers in expanding market reach and raising awareness about hydroponics in the community. The main problem is the lack of education about hydroponics among the public. In addition, the creation of applications is often complicated, difficult to set up, and difficult to test. However, with BLoC state management, we can separate the appearance and logic of the app, make the code easier to understand, and improve the quality of the app. The software development method used in this research is waterfall. The result was application that provides various educational features, including videos, articles, recipes, and interactive quizzes. This quiz helps users test their knowledge about the health benefits of vegetables and fruit, while the recipe feature provides information about ingredients and how they are prepared. Results from questionnaire testing showed that 91% of respondents found the app useful. With this high level of satisfaction, it can be concluded that this application is very useful for users.